1998
DOI: 10.1128/jb.180.10.2701-2710.1998
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of Three Streptococcus pneumoniae Transformation-Specific Loci by Use of a lacZ Reporter Insertion Vector

Abstract: Although more than a dozen new proteins are produced whenStreptococcus pneumoniae cells become competent for genetic transformation, only a few of the corresponding genes have been identified to date. To find genes responsible for the production of competence-specific proteins, a random lacZ transcriptional fusion library was constructed in S. pneumoniae by using the insertional lacZ reporter vector pEVP3. Screening the library for clones with competence-specific β-galactosidase (β-Gal) production yielded thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
67
0
1

Year Published

1999
1999
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(73 citation statements)
references
References 60 publications
5
67
0
1
Order By: Relevance
“…the proteins involved in binding, processing, uptake and integration of DNA. The work of Campbell et al (1998) and Pestova and Morrison (1998) has demonstrated that the late genes share a common regulatory sequence called the competence-induced promoter Q 1999 Blackwell Science Ltd, Molecular Microbiology, 33, 817±827 (CIP) consensus sequence. This sequence is unrelated to the sequence recognized by ComE, showing that ComE activates transcription of the late genes via one or more intermediate factors.…”
Section: Discussionmentioning
confidence: 99%
“…the proteins involved in binding, processing, uptake and integration of DNA. The work of Campbell et al (1998) and Pestova and Morrison (1998) has demonstrated that the late genes share a common regulatory sequence called the competence-induced promoter Q 1999 Blackwell Science Ltd, Molecular Microbiology, 33, 817±827 (CIP) consensus sequence. This sequence is unrelated to the sequence recognized by ComE, showing that ComE activates transcription of the late genes via one or more intermediate factors.…”
Section: Discussionmentioning
confidence: 99%
“…Both of these ComEA orthologues are situated immediately upstream from an open reading frame that encodes an orthologue of ComEC. In the case of S. pneumoniae, this operon is required for transformation (Campbell et al, 1998;Pestova and Morrison, 1998). ComEA is 28.5% identical (60% similar) to MTCY253.05 and 37.8% identical (72.7% similar) to the streptococcal protein.…”
Section: Discussionmentioning
confidence: 99%
“…Thermus thermophilus ComEA orthologs are present in different transformable bacteria such as B. subtilis, N. gonorrhoeae, Campylobacter jejuni and S. pneumoniae (Pestova & Morrison, 1998;Provvedi & Dubnau, 1999;Chen & Gotschlich, 2001;Jeon & Zhang, 2007). In contrast to the membrane localization of ComEA in B. subtilis, the neisserial and Campylobacter ortholog, ComE and Cj0011c, respectively, are located in the periplasm.…”
Section: Mechanism Of Dna Translocationmentioning
confidence: 99%